Multidimensional assessment of adverse events of finasteride：a real-world pharmacovigilance analysis based on FDA Adverse Event Reporting System (FAERS) from 2004 to April 2024 - Xiaoling Zhong; Yihan Yang; Sheng Wei; Yuchen Liu (PLoS ONE, 2025)
Background Finasteride is commonly utilized in clinical practice for treating androgenetic alopecia, but real-world data regarding the long-term safety of its 0adverse events(AEs) remains incomplete, necessitating ongoing supplementation. This study aims to evaluate the AEs associated with finasteride use, based on data from the US Food and Drug Administration Adverse Event Reporting System (FAERS), to contribute to its safety assessment. Methods We reviewed AE reports associated with finasteride from the US Food and Drug Administration Adverse Event Reporting System database, covering the period from the first quarter of 2004 to the first quarter of 2024. We assessed the safety of finasteride medication and AEs using four proportional disproportionality analyses: reported odds ratio (ROR), proportionate reporting ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPN), and Multi-Item Gamma Poisson Shrinkage (MGPS). These methods were used to evaluate whether there is a significant association between finasteride drug use and AEs. To investigate potential safety issues related to drug use, we further analyzed the similarities and differences in the onset time and AEs by sex, as well as the similarities and differences in AEs by age. Results A total of 11,557 AE reports in which finasteride was the primary suspected drug were analysed. The majority of patients were male (86.04%) and a significant proportion were young adults aged 18-45 years (27.22%). A total of 73 different AEs were categorised into 7 system organ classes (SOCs), with common AEs including erectile dysfunction and sexual dysfunction. In addition, we identified previously unlisted AEs, including Peyronie’s disease and post-5α reductase inhibitor syndrome. Of the reported AEs, 102 occurred in men and 7 in women, with depression and anxiety being significant AEs observed in both sexes. When analysed by age group, there were 17 AEs in patients aged ≤ 18 years, 157 in patients aged 18-65 years and 133 in patients aged ≥ 65 years. Common AEs in all age groups included erectile dysfunction, decreased libido, depression, suicidal ideation, psychotic disturbances and attention disorders. The median time to onset of all AEs was 61 days, with the majority occurring within the first month of treatment. Notably, a significant number of AEs persisted beyond one year of treatment. Conclusion The results of our study uncovered both known and novel AEs associated with finasteride medication. Some of these AEs were identical to the specification, and some of them signaled AEs that were not demonstrated in the specification. In addition, some AEs showed variations based on sex and age in our study. Consequently, our findings offer valuable insights for future research on the safety of finasteride medication and are anticipated to enhance its safe use in clinical practice.